The First Sale Theory of the Right of Distribution and its Application in a Digital Environment - Plana Perillán, Javiera (Revista Chilena de Derecho y Tecnología, 2016)
The first sale theory allows the massive entry to the public of works protected by copyright. With the uptake of the internet, the implementation of this theory, as well as their traditional effects are put in doubt, so it is necessary to review the scope and conditions of application of the exhaustion, to determine if it is feasible or not to adapt it to the digital environment. In this research the author approach this conflict, reviewing the context in which the exhaustion of the right of distribution involves and the main obstacles that arise with the change of the digital environment. Finally, she argues that it is possible to implement a theory of the exhaustion on the internet.